Handbook of research on smart technology models for business and industry - Thomas, J. Joshua; Fiore, Ugo; Perez Lechuga, Gilberto; Kharchenko, Valeriy 1938- (IGI Global, 2020)
"This book discusses relevant abstract frameworks and the latest experimental research findings in theory, mathematical models, software applications, and prototypes in the area of smart technologies"--